Drosophila, the golden bug, emerges as a tool for human genetics. - Bier, E. (Nature Reviews. Genetics, 2005)
Drosophila melanogaster is emerging as one of the most effective tools for analyzing the function of human disease genes, including those responsible for developmental and neurological disorders, cancer, cardiovascular disease, metabolic and storage diseases, and genes required for the function of the visual, auditory and immune systems. Flies have several experimental advantages, including their rapid life cycle and the large numbers of individuals that can be generated, which make them ideal for sophisticated genetic screens, and in future should aid the analysis of complex multigenic disorders. The general principles by which D. melanogaster can be used to understand human disease, together with several specific examples, are considered in this review.